Cystic Fibrosis–Associated Liver Disease in Lung Transplant Recipients. Issue 8 (25th June 2019) - Mallea, Jorge; Bolan, Candice; Cortese, Cherise; Harnois, Denise
Abstract : Cystic fibrosis (CF) is an autosomal recessive disease characterized by mutations in the gene that encodes for the cystic fibrosis transmembrane conductance regulator protein (CFTR). CFTR gene mutations manifest as epithelial cell dysfunction in the airways, biliary tract, pancreas, gut, sweat glands, paranasal sinuses, and genitourinary tract. The clinical manifestations of this dysfunction include respiratory tract infections, bronchiectasis, pancreatic insufficiency, malabsorption, intestinal obstruction, liver disease, and male infertility. The liver disease manifestations of CF can include biliary disease, multilobular cirrhosis, and portal hypertension with and without cirrhosis. Pulmonary disease is the main cause for morbidity and mortality in individuals with CF, and according to the International Society for Heart and Lung Transplantation, CF is the third most common indication for lung transplantation in adults, accounting for 16% of procedures performed. The survival after lung transplantation in individuals with CF continues to improve and is now the highest among end‐stage lung diseases requiring transplant. The survival rate at 10 years is close to 50%. Given the potential presence of liver disease in CF patients undergoing an evaluation for lung transplantation and in lung transplant recipients, it is important to understand the manifestations of liver disease in CF patients and the recommended workup and follow‐up. This review aims to discuss the current literature and provide guidance in the management of these patients.